Timing of Release Influence Breeding Success of Translocated Captive-Bred Migrant Asian Houbara Bustard - Azar, Joseph F.; Ferlat, Cédric; Landsmann, Cécile; Hingrat, Yves (Frontiers in Conservation Science, 2022)
In conservation translocation, released animals should have comparable fitness to their wild counterparts to effectively contribute to the species demography. Captive-bred animals frequently exhibit lower fitness performances, which can often be attributed to an inadequate release strategy. Untimely release of migrant animals may interfere with key events such as their migration and breeding. In Kazakhstan and Uzbekistan, declining wild populations of Asian houbara (Chlamydotis macqueenii) are reinforced in their breeding grounds with captive-bred individuals. Using data from 6 years of monitoring, we compare eight breeding traits and the productivity of wild and captive-bred females released in two distinct seasons (autumn vs. spring) considering the effects of age and time in the season. Females released in the spring nest prior to their first migration, and females released in the autumn nest following their first migration. Our results highlight that captive-bred and wild females have similar breeding traits and productivity. Breeding probability, laying date, and egg volume varied, depending on the release season and female age. One-year-olds released in autumn have a significantly lower breeding probability compared to wild and spring-released females. However, 1-year-old females released in the spring nest later and lay smaller eggs than wild and autumn-released birds; effects which appear to be carried over with age. Age has a positive effect on breeding probability, egg volume, re-clutching probability and advancement of nesting date. These findings suggest a complex interplay of release timing with migration and breeding, resulting in short- and long-term effects on population demography, emphasizing its importance in conservation translocation.